External effects of education on earnings: Swedish evidence using matched employee-establishment data - Gunnar Isacsson (Institute for Labour Market Policy Evaluation (IFAU), 2005)
This paper provides an empirical investigation of externalities from education in Sweden in an earnings equation framework. The empirical models are estimated on a large sample of matched employees and establishments. External effects of education are identified from the average educational attainment of workers outside the individual's establishment. The paper also investigates the coherence of the evidence with respect to the idea that educational externalities arise through face-to-face interaction between individuals. A set of different specifications and fixed effects models is used to investigate the robustness of the basic cross-sectional model. The cross-sectional models suggest, in general, that externalities are positive and significantly different from zero. The cross-sectional evidence is also broadly coherent with the idea that externalities are declining in spatial transaction costs, such as the Euclidean distance between establishments. However, after accounting for individual fixed effects and dummy variables for the county in which the individual works the results indicate no statistically significant external effects of education on earnings in Sweden.
Keywords: I20; 330; Education; earnings; Weiterbildung; Externer Effekt; Schätzung; Schweden